A purification method for tag-free human cystatin C recombinant protein expressed in Escherichia coli. Issue 2 (7th February 2017) - Chen, Te; Xu, Wenchun
ABSTRACT: To obtain recombinant cystatin C (CysC) protein, which can be used in immunological diagnostic kits, we focused on the preparation of tag-free CysC. The 6 × His–TF–CysC fusion protein was found to overexpress in soluble form in cells of BL21-Gold (DE3)/pCold TF–CysC, which had been induced with isopropyl-D-1-thiogalactopyranoside. Subsequently, we established a protein purification method for tag-free CysC using immobilized metal-affinity chromatography and size-exclusion chromatography. In this method, glutathione-S-transferase–human rhinovirus 3C proteases were used to remove the protein tags. High homogeneity of the purified CysC was determined by SDS-PAGE, while the purity of the tag-free CysC was ascertained to be above 95%. With a yield of 25 mg/L from bacterial culture, the biological activity of the tag-free CysC was evaluated as inhibitors like natural CysC. The performance of this purification method was successfully evaluated in the preparation of other low molecular weight heterologous proteins in Escherichia coli .